Prolactin does not seem to mediate the improvement on insulin resistance markers and blood glucose levels related to breastfeeding - Oliveira, Julia Martins de; Dualib, Patricia Medici; Ferraro, Alexandre Archanjo; Carvalho, Camila Rodrigues de Souza; Mattar, Rosiane; Dib, Sérgio Atala; Almeida-Pititto, Bianca de (Frontiers in Endocrinology, 2023)
Introduction The prevalence of type 2 diabetes mellitus (T2DM) is increasing worldwide. Strategies to decrease this risk should be strongly encouraged. Lactation has been associated, for the mother, with reduction in future T2DM risk in several studies. The mechanisms behind this phenomenon, however, are poorly understood. The aims of this study were, first, to compare blood glucose levels and markers of insulin resistance (MIR) in early postpartum women with overweight/obesity according to their breastfeeding status and, second, to evaluate whether prolactin (PRL) levels could mediate improvements in these parameters. Methods The prospective study followed 95 women older than 18 years from early pregnancy for up to 60 to 180 days postpartum. All participants had a BMI > 25 kg/m2 and a singleton pregnancy. At each visit, questionnaires and clinical and biochemical evaluations were performed. Participants were divided into two groups according to the breastfeeding status as “yes” for exclusive or predominant breastfeeding, and “no” for not breastfeeding. Results Breastfeeding women (n = 44) had significantly higher PRL levels [47.8 (29.6–88.2) vs. 20.0 (12.0–33.8), p< 0.001]. They also had significantly lower fasting blood glucose levels [89.0 (8.0) vs. 93.9 (12.6) mg/dl, p = 0.04], triglycerides (TG) [92.2 (37.9) vs. 122.4 (64.4) mg/dl, p = 0.01], TG/HDL ratio [1.8 (0.8) vs. 2.4 (1.6) mg/dl, p = 0.02], TyG index [8.24 (0.4) vs. 8.52 (0.53), p = 0.005], fasting serum insulin [8.9 (6.3–11.6) vs. 11.4 (7.7–17.0), p = 0.048], and HOMA-IR [2.0 (1.3–2.7) vs. 2.6 (1.6–3.9), p = 0.025] in the postpartum period compared to the non-breastfeeding group. Groups were homogeneous in relation to prevalence of GDM, pre-gestational BMI, as well as daily caloric intake, physical activity, and weight loss at postpartum. Linear regression analysis with adjustments for confounders showed a statistically significant association of breastfeeding with fasting blood glucose [−6.37 (−10.91 to −1.83), p = 0.006], HOMA-IR [−0.27 (−0.51 to −0.04), p = 0.024], TyG index [−0.04 (−0.06 to −0.02), p = 0.001], and TG/HDL ratio [−0.25 (−0.48 to −0.01), p = 0.038]. Mediation analysis showed that PRL did not mediate these effects. Sensitivity analyses considering different cutoffs for PRL levels also did not show modification effect in the mediation analyses. Conclusion Breastfeeding was associated with improvement in glucose metabolism and MIR 60 to 180 days after birth in overweight and obese women, even when adjusted for confounders. PRL levels were not found to mediate the association between breastfeeding and improvement in MIR.